From Case Compensation to Model Export: A Study on the Iteration Process, Core Experience and National Promotion Feasibility of the Public Welfare Study Tour Project "Dream Journey with Spiritual Companionship" in Heilongjiang Province - Liping Liu; Bin Yu (Education Research on Study Tours and Practice, 2026)
Having undergone five rounds of iteration from 2021 to 2025, the public welfare study tour project Dream Journey with Spiritual Companionship in Heilongjiang Province has evolved from a single caring activity for left-behind children into an integrated model featuring practical education, psychological empowerment and social support. Based on empirical data of the five sessions of the project, this paper systematically reviews its evolutionary process from individual case support to standardized model output, and summarizes four core experiences: policy anchoring, professional foundation laying, technological empowerment and ecological collaboration. The research shows that by accurately aligning with the national strategy for children’s development, constructing a standardized curriculum system supported by teaching and research, and innovating the psychological intervention mechanism for special groups, the project has formed a replicable paradigm of public welfare study tours. Its promotion value lies in providing a low-cost and high-satisfaction implementation path for practical education of special groups in the new era, and offering important policy implications for promoting educational equity and social harmony.